Impact of Stator Resistance Unbalance on the Efficiency and Torque of Three-Phase Induction Motor - Muhamad Vickry Almuhtadi Billah; Siti Anisah; Parlin Siagian (Jurnal Info Sains : Informatika dan Sains, 2026)
Three-phase induction motors are the main components in industrial power systems; However, their performance is vulnerable to internal disturbances such as stator resistance imbalance caused by aging, overheating, or manufacturing defects. This study aims to regularly analyze the impact of stator resistance imbalance on the efficiency and torque characteristics of a squirrel-cage induction motor using mathematical modeling based on an equivalent circuit. Unlike previous studies that employed external resistors, this research directly modifies the stator resistance parameters in the model to represent more realistic internal degradation. Simulations were conducted on a 3.73 kW, 400 V, 50 Hz motor with stator resistance imbalance variations ranging from 0% to 20%. The results show that the imbalance causes uneven current distribution and an increase in stator copper losses of up to 5.94% at the 20% imbalance condition, although the current imbalance percentage remains below 1%. As a result, the efficiency decreases linearly from 92.97% to 92.62%, while the mechanical torque experiences a slight reduction from 95.88 Nm to 95.28 Nm. This phenomenon also has the potential to increase torque ripple and uneven heating. The study demonstrates that even small stator resistance imbalances have a significant impact on motor performance and lifespan, and therefore should be considered in predictive maintenance strategies and energy efficiency optimization.